Human reproductive instincts - Viliūnas, Vytis (Psichologija, 2006)
The article discusses the data on the instinctive basis for human reproductive behavior that have mainly been gathered in evolutionary psychology research. At the beginning of the article, the concept of the instinct is briefly touched upon. It is primarily based on the ideas raised by W. McDougall and W. James (these ideas being grounded on specific and not widely acnowledged understanding of instinct’s evolutionary development). According to this understanding, with instincts phylogenetically changing, their receptive component, which causes instinctive reactions, and reactive component were becoming increasingly less definite and thus left open to learning processes, with the emotional component surviving and developing. As a result of such evolutionary trend, instinct as a form of behavior gradually modified into instinct as a complex inherited motivation expressed by emotions. The sum of interrelated inherited emotions is the chief result of the evolutionary development of the instinct. A number of data of human sexual behavior is discussed in order to ground such understanding: (1) an increased significance of human sexual instinct toconsolidate the consequences of anthropogenesis, the development of which was rapid in comparison to the established pace of evolution; (2) mutual influence between sexual instinct and its further social development; (3) data on waist-to-hip ratio and fluctuating asymmetry research; (4) the influence of human odour in selecting a sexual partner, including the one matching genetically (histologically); (5) interpretation of sexual deviations as an extreme expression of instincts; a.o. The following rule of deviation argument has been put forward: if the pattern of a certain psychopathological deviation has been observed throughout all historical times and all cultures, which means that it cannot be explained by the cultural specifics of humandevelopment, its genetic origin should be questioned; if such a symptom is related to motivation, it is predetermined by instinct. Discussing the instinctive basis for relationship between mother and infant the article features data gathered from many researches which reveal that at birthtime an infant is already prepared for the necessary emotional communication and relationships with close adults. The article provides examples and arguments (for instance, on the development of baby talk and the en face phenomenon) showing that the negation of motherhood instinct has no factual foundation; it is rather based on ideological beliefs, such as those of feminism. The article separately describes and discusses other instincts that are connected with the relationship between an adult and an infant but have a broader expression: tending instinct (Taylor, 2002), instinct to teach (Barnett, 1977; Whiting, 1963) and language instinct (Pinker, 1995). Besides, it discusses stages of an infant’s adoption of phonemic, intonational language, as well as data on universal grammar, mental language, children’s role in the process of primitive pidgin pseudo-languages’ transformation into developed creoles languages, etc.
Keywords: human instincts; sexuality; mothering; tending; deviations